Hollow microsphere with low thermal conductivity and low emissivity as well as preparation method and application of hollow microsphere

By adopting a hollow microsphere structure composed of a hollow core, a glass spherical shell, a porous silicon oxide layer and a metal area physically isolated from each other, the problem that hollow microspheres in the prior art is difficult to take into account both mechanical stability, low thermal conductivity and low emissivity, and good coordinated control of heat conduction and heat radiation heat transfer is achieved.

CN119505570AActive Publication Date: 2025-02-25TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311067860.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-02-25
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

Existing hollow microspheres are difficult to take into account high mechanical stability, low thermal conductivity and low emissivity, resulting in insufficient coordinated control capabilities of heat conduction and heat radiation heat transfer.

Method used

A hollow microsphere structure consisting of a hollow core, a glass spherical shell, a porous silicon oxide layer and a metal layer is adopted. The metal layer consists of metal areas that are physically isolated from each other. By adjusting the metal coverage and layer structure, low thermal conductivity and low emissivity are achieved.

Benefits of technology

The hollow microspheres are achieved with low density, high mechanical stability, low thermal conductivity and low emissivity, and have good coordinated control capabilities for thermal conduction and thermal radiation heat transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505570A_ABST
    Figure CN119505570A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow microsphere with low thermal conductivity and low emissivity as well as a preparation method and application of the hollow microsphere. The structure of the hollow microsphere comprises a hollow core, and a glass ball shell layer, a porous silicon oxide layer and a metal layer which are sequentially arranged from inside to outside, wherein the metal layer is composed of a plurality of metal areas which are physically isolated from one another. The hollow microsphere has low density, high mechanical stability, low thermal conductivity and low emissivity, and has good cooperative control capability of thermal conduction and thermal radiation heat transfer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of powder materials, and more specifically to a hollow microsphere having both low thermal conductivity and low emissivity, and a preparation method and application thereof. Background Art

[0002] While scientific researchers and technical developers are striving to find alternative energy sources, especially green renewable energy, they are also focusing on the research and development of efficient energy utilization. For efficient energy utilization, in addition to improving the energy efficiency of production processes and equipment, another important focus is to achieve efficient storage and utilization of energy with the help of high-efficiency thermal insulation materials, and reduce energy consumption while meeting production and living needs. A typical example is the insulation of various storage equipment, pipelines and buildings. High-efficiency thermal insulation materials can effectively improve insulation efficiency and reduce energy loss, which not only saves energy, but also reduces the release of heat into the environment and reduces secondary hazards.

[0003] Naturally occurring thermal insulation materials and artificial thermal insulation materials mostly achieve low heat conductivity through porous or hollow structures containing pores. For artificial materials, the controllability of their pore structure and the designability of their chemical composition provide the possibility of improving the thermal insulation effect. For example, the template material can be introduced into the inorganic material phase formation and aggregation molding process by using an additive (organic molecules, water, etc.) that plays a template role, and then the template is removed by extraction or heat treatment to obtain porous thermal insulation materials with various macroscopic forms and microscopic pore structures. In addition, the polymer and other matrices are physically or chemically foamed during the curing or cross-linking molding process, and pores can be introduced into them. By controlling the reaction conditions, the pore content, structure and distribution state can be greatly controlled, thereby obtaining thermal insulation materials with different properties. It is worth mentioning that the above two methods of constructing pore structures are to manufacture pores in situ during the material molding process. Since it is necessary to take into account the molding of the matrix material and the formation of pores, the preparation process is often cumbersome, and the pore control is difficult, which is not conducive to accurate pore structure control and high-efficiency large-scale production. In view of this, researchers have developed a method of introducing pores into thermal insulation materials through hollow microsphere fillers in recent years. This method uses pre-formed hollow microspheres as the source of pores, which can not only easily realize the regulation of pore content, size and distribution state, but also can use the spherical shell of the hollow microspheres to reinforce the pore wall to achieve the mechanical reinforcement of such filler-type thermal insulation materials (composite materials), which is conducive to obtaining composite thermal insulation materials with excellent thermal insulation effect and mechanical strength. However, the efficient molding, mechanical stability and thermal insulation effect of the above-mentioned filler-type thermal insulation composite materials largely rely on pre-formed hollow microspheres, and the current hollow microspheres still have difficulty in taking into account high mechanical stability, low thermal conductivity and low emissivity, and the ability to coordinate heat conduction and thermal radiation heat transfer is insufficient. Summary of the invention

[0004] Based on the above facts, the purpose of the present invention is to provide a hollow microsphere with low thermal conductivity and low emissivity, and a preparation method and application thereof. The hollow microsphere has low density, high mechanical stability, low thermal conductivity and low emissivity, and has good synergistic control capabilities of heat conduction and thermal radiation heat transfer.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] On the one hand, the present invention provides a hollow microsphere with low thermal conductivity and low emissivity, wherein the structure of the hollow microsphere comprises a hollow core, and a glass shell layer, a porous silicon oxide layer and a metal layer arranged in sequence from the inside to the outside;

[0007] The metal layer is composed of a plurality of metal regions which are physically isolated from each other.

[0008] In addition, it can be understood that in the hollow microspheres, the glass shell layer and the porous silicon oxide layer are both continuous layer structures.

[0009] In the technical solution of the present invention, the intermediate porous silicon oxide layer can be firmly combined with the glass sphere shell layer and the metal layer to further improve the mechanical stability of the hollow microsphere, and on the other hand, can better achieve low heat conductivity.

[0010] In addition, in the metal layer, each metal region is physically isolated from each other, that is, they do not touch each other and present an isolated island structure. This metal layer composed of physically isolated metal regions not only reduces the emissivity of the obtained hollow microspheres, but also overcomes the conventional problem of increased thermal conductivity due to the introduction of metal.

[0011] In the technical solution, there is no requirement for the distance between the metal regions constituting the metal layer, and the distance between them can be kept greater than 0 and not in contact.

[0012] Further, the metal coverage of the metal layer is 30-70%. Exemplarily, the metal coverage of the metal layer includes but is not limited to 35-70%, 37-70%, 35-40%, 37-40%, 38-40%, 37%, 38%, 39%, 40%, etc. The hollow microspheres obtained at this time have good mechanical stability, low thermal conductivity and low emissivity.

[0013] The metal coverage refers to the coverage ratio of the metal layer to the outer surface area of ​​the porous silicon oxide layer. Further, the metal region is composed of one or more of metal nickel, cobalt, iron, copper and silver. Preferably, the metal region is composed of metal silver. The hollow microspheres obtained at this time have both lower emissivity and low thermal conductivity.

[0014] Furthermore, in terms of mass percentage, the hollow microspheres contain 45-80 wt % of a glass shell layer, 10-35 wt % of a porous silicon oxide layer and 10-35 wt % of a metal layer.

[0015] In some examples, in the hollow microspheres, the mass percentage of the porous silicon oxide layer includes but is not limited to 14-25wt%, 20-25wt%, 14.3wt%, 20wt%, 25wt%, etc., and the obtained hollow microspheres have suitable mechanical stability, low thermal conductivity and low emissivity.

[0016] In some examples, in the hollow microspheres, the mass percentage of the glass shell layer includes but is not limited to 60-75wt%, 60-72wt%, 60-70wt%, 62.5wt%, 66.7wt%, 71.4wt%, etc., and the obtained hollow microspheres have suitable mechanical stability, low thermal conductivity and low emissivity.

[0017] In some examples, in the hollow microspheres, the mass percentage of the metal layer includes but is not limited to 10-15wt%, 12-15wt%, 12-14.5wt%, 12.5wt%, 13.3wt%, 14.3wt%, etc., and the obtained hollow microspheres have suitable mechanical stability, low thermal conductivity and low emissivity.

[0018] Furthermore, the density of the hollow microspheres is 0.25-0.9 g / cm 3 , average diameter is 15-80μm, specific surface area is 50-200m 2 / g. It should be noted that the "diameter" here refers to the diameter of the outer surface of the hollow microsphere.

[0019] For example, the density of the hollow microspheres includes, but is not limited to, 0.4-0.9 g / cm 3 , 0.4-0.6g / cm 3 , 0.5-0.6g / cm 3 , 0.41-0.59g / cm 3 , 0.41g / cm 3 , 0.51g / cm 3 , 0.54g / cm 3 , 0.59g / cm 3 Etc. The hollow microspheres obtained at this time have suitable mechanical stability, low thermal conductivity and low emissivity.

[0020] Exemplarily, the average diameter of the hollow microspheres includes, but is not limited to, 40-50 μm, 40-45 μm, 40-41 μm, etc. The hollow microspheres obtained at this time have suitable mechanical stability, low thermal conductivity and low emissivity.

[0021] Furthermore, the porous silicon oxide layer is made of porous silicon dioxide, the porosity of the porous silicon dioxide is 59.8%, and the average pore size is 2.7 nm.

[0022] In another aspect, the present invention provides a method for preparing the hollow microspheres as described above, comprising the following steps:

[0023] Assembling porous silicon oxide precursor on the surface of glass hollow microspheres to obtain microspheres A;

[0024] The metal precursor is coated on the surface of microsphere A to obtain microsphere B;

[0025] The microspheres B are heat-treated in a reducing atmosphere to obtain the hollow microspheres.

[0026] In the above preparation method, the glass hollow microspheres are products obtained after flotation treatment. The method specifically comprises the following steps:

[0027] The hollow microspheres with glass shells (glass hollow microspheres) are immersed in water, the floating hollow microspheres are collected, and the floating hollow microspheres are dried to obtain the glass hollow microspheres after flotation treatment.

[0028] Furthermore, the density of the glass hollow microspheres is 0.2-0.5 g / cm 3 In some specific examples, the density of the glass hollow microspheres includes but is not limited to 0.2-0.5 g / cm 3 , 0.3-0.4g / cm 3 , 0.35-0.4g / cm 3 , 0.38g / cm 3 Etc. The hollow microspheres obtained at this time have good comprehensive properties.

[0029] Furthermore, the hollow microspheres with silicate glass shells can be purchased from commercial sources or prepared by methods known in the art. There is no particular limitation on the structural dimensions of the hollow glass microspheres with silicate glass shells. For the purpose of the invention of this application, the thickness of the glass shell layer (silicate shell) can be 0.3-2 μm.

[0030] Furthermore, the ratio of the glass hollow microspheres to water in the flotation treatment is 1:10-1:3.

[0031] Furthermore, the method for assembling a porous silicon oxide precursor on the surface of a glass hollow microsphere to obtain microsphere A comprises the following steps:

[0032] After mixing the glass hollow microspheres with the treatment solution A, a mixed solution of tetraethyl orthosilicate and anhydrous ethanol is added, and then reacting at room temperature for 20-60 minutes to obtain the microspheres A;

[0033] The treatment solution A is composed of 1-3 g hexadecyltrimethylammonium bromide, 50-100 mL water, 60-120 mL anhydrous ethanol, 8-15 mL concentrated ammonia water and 0.02-0.05 g sodium chloride;

[0034] The mass ratio of the glass hollow microspheres to the hexadecyltrimethylammonium bromide in the treatment solution A is 2:1;

[0035] The volume ratio of water to tetraethyl orthosilicate and anhydrous ethanol in the treatment liquid A is 80:(2-10):(10-25).

[0036] By controlling the composition of the treatment liquid A, the glass hollow microspheres, the treatment liquid A, the amounts of tetraethyl orthosilicate and anhydrous ethanol, and the combination of the components, the porous silicon oxide precursor assembled on the surface of the glass hollow microspheres has a dense structure and an appropriate pore size, and is more conducive to the subsequent adhesion and bonding of the metal, thereby obtaining metal regions that are physically separated from each other, further improving the structural stability, and improving the mechanical properties of the microspheres and the low thermal conductivity and low emissivity.

[0037] Furthermore, the treatment liquid A is composed of a mixture of 2 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride.

[0038] Furthermore, the step of preparing microspheres A further comprises the steps of filtering and drying after reacting at room temperature.

[0039] Furthermore, the method for coating the surface of microsphere A with a metal precursor to obtain microsphere B comprises the following steps:

[0040] After mixing the microsphere A with the treatment liquid B, reacting them in an air atmosphere at a temperature of 400-600° C. for 60 minutes to obtain the microsphere B;

[0041] The treatment liquid B is obtained by mixing a soluble salt of a metal with a water-soluble organic matter and water in a mass ratio of 10: (6-9): 5. The treatment liquid B can be used to coat the metal precursor on the microspheres (and then obtain the metal through a reducing heat treatment); the organic matter decomposes and escapes during the heat treatment, assisting the coating and island distribution of the metal precursor.

[0042] Furthermore, in the method for obtaining microspheres B, the reaction temperature includes but is not limited to 450-550° C., 500° C., etc. This helps to obtain hollow microspheres with stable structures.

[0043] Furthermore, the water-soluble organic matter is selected from at least one of sucrose, starch and citric acid.

[0044] Furthermore, the soluble metal salt is selected from metal nitrates and / or metal organic acid salts.

[0045] Furthermore, the step of preparing microspheres B further includes a step of sieving and dispersing after the reaction. The sieving and dispersing method is preferably to grind and press the reaction product on a 50-300 mesh standard sieve to disperse the product and pass it through the sieve holes.

[0046] Furthermore, the reducing atmosphere is hydrogen or a mixture of hydrogen and argon.

[0047] Furthermore, the heat treatment temperature is 400-600°C, and the heat treatment time is 1-6 hours. In some examples, the heat treatment temperature includes but is not limited to 450-550°C, 500°C, etc. This helps to obtain structurally stable hollow microspheres.

[0048] Furthermore, the method further comprises the step of sieving and dispersing after the heat treatment. The sieving and dispersing method is preferably to grind and press the reaction product on a 50-300 mesh standard sieve to disperse the product and pass through the sieve holes.

[0049] In the preparation method of hollow microspheres provided in the technical solution of the present invention, commercial glass hollow microspheres are preferably used as carriers, and firstly, silicon oxide spherical shells are assembled on their surfaces by hydrolysis deposition reaction assisted by templates, and then metal spherical shells are further assembled by chemical reduction method assisted by seed cores; subsequently, the template inside the silicon oxide spherical shells is removed and the metal spherical shell assembly units are aggregated by heat treatment to form a spherical shell structure with granular distribution. This method has the effect of efficient molding.

[0050] In yet another aspect, the present invention provides use of the hollow microspheres as described above in powder thermal insulation and thermal insulation fillers.

[0051] The beneficial effects of the present invention are as follows:

[0052] The hollow cavities inside the hollow microspheres provided in the present invention reduce the overall density and thermal conductivity of the hollow microspheres; a porous silicon oxide material with low thermal conductivity is used as the second layer of continuous spherical shell to reduce the thermal conductivity of the spherical shell; and a unique island-shaped (non-interconnected) metal structural unit is used to not only reduce the overall infrared emissivity of the microspheres, but also avoid a significant increase in thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0054] Figure 1 A schematic diagram showing the structure of the hollow microspheres with both low thermal conductivity and low emissivity in the present invention.

[0055] Figure 2A schematic diagram of the preparation process of hollow microspheres with low thermal conductivity and low emissivity in the present invention is shown.

[0056] Figure 3 A low-magnification SEM image of the hollow microspheres prepared in Example 5 is shown.

[0057] Figure 4 A high-magnification SEM image of the hollow microspheres prepared in Example 5 is shown.

[0058] Figure 5 The X-ray diffraction pattern of the hollow microspheres prepared in Example 5 is shown. DETAILED DESCRIPTION

[0059] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0060] In a specific embodiment of the present invention, the structure diagram of the obtained hollow microspheres with both low thermal conductivity and low emissivity is as follows Figure 1 The schematic diagram of its preparation process is shown in Figure 2 shown.

[0061] Example 1

[0062] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0063] The density is 0.46g / cm 3 Glass hollow microspheres.

[0064] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0065] (2) adding 4 g of hollow microspheres A to a treatment solution A consisting of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0066] (3) adding a mixed solution containing 8 mL of tetraethyl orthosilicate and 20 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0067] (4) Mix 10 g of silver nitrate, 8 g of sucrose and 5 g of water in a beaker, heat in a water bath at 45°C, and stir magnetically until completely dissolved to obtain treatment solution B;

[0068] (5) mixing the hollow microspheres B with 8 g of treatment solution B, and then treating them at 600° C. for 60 min in an air atmosphere. After the reaction, the microspheres were dispersed through an 80-mesh sieve to obtain hollow microspheres C;

[0069] (6) The hollow microspheres C are heat treated in a 5% H2-95% Ar atmosphere at 400°C for 3 h to obtain the target product, which is a hollow microsphere with low thermal conductivity and low emissivity (the shell layer is a glass ball shell layer, a porous silicon oxide layer and a metal layer arranged in sequence from the inside to the outside).

[0070] The mass percentages of the glass shell layer, porous silicon oxide layer (porosity 59.8%, average pore size 2.7 nm) and metal layer in the hollow microspheres obtained in this example are 51%, 24% and 25% respectively. Other structural and performance parameters are shown in Table 1.

[0071] In this specific implementation, the hollow microsphere performance test method is as follows:

[0072] 1) Density is tested using Archimedes principle;

[0073] 2) The strength is evaluated by isostatic pressing treatment, and the test is carried out according to the patent "A method for determining the isostatic strength of hollow glass microspheres" (201410196976.0);

[0074] 3) Thermal conductivity is tested in powder form using a thermal constant analyzer;

[0075] 4) The emissivity is tested in powder form using an infrared emissivity tester;

[0076] 5) The oxide particle coverage was obtained by SEM photo analysis using imageJ software;

[0077] 6) The specific surface area is tested using a surface area and porosity tester.

[0078] Example 2

[0079] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0080] The density is 0.38g / cm 3 Glass hollow microspheres.

[0081] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0082] (2) adding 4 g of hollow microspheres A to a treatment solution A consisting of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0083] (3) adding a mixed solution containing 3.2 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0084] (4) 10 g of cobalt nitrate, 7 g of sucrose and 5 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution B;

[0085] (5) The hollow microspheres B obtained in step (3) were mixed with 9 g of treatment solution B, and then treated at 500° C. for 60 min in an air atmosphere. After the reaction, the microspheres were dispersed through an 80-mesh sieve to obtain hollow microspheres C;

[0086] (6) The hollow microspheres C are heat treated in a 5% H2-95% Ar atmosphere at 500°C for 3 h to obtain the target product, which is a hollow microsphere with low thermal conductivity and low emissivity (the shell layer is a glass ball shell layer, a porous silicon oxide layer and a metal layer arranged in sequence from the inside to the outside).

[0087] The mass percentages of the glass shell layer, porous silicon oxide layer and metal layer in the hollow microspheres obtained in this example are 71.4%, 14.3% and 14.3% respectively. Other structural and performance parameters are shown in Table 1.

[0088] Example 3

[0089] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0090] The density is 0.38g / cm 3 Glass hollow microspheres.

[0091] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0092] (2) adding 4 g of the hollow microspheres A obtained in step (1) to a treatment solution A composed of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0093] (3) adding a mixed solution containing 4.8 mL of tetraethyl orthosilicate and 13 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0094] (4) 10 g of cobalt nitrate, 7 g of sucrose and 5 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution B;

[0095] (5) The hollow microspheres B obtained in step (3) were mixed with 9 g of treatment solution B, and then treated at 500° C. for 60 min in an air atmosphere. After the reaction, the microspheres were dispersed through an 80-mesh sieve to obtain hollow microspheres C;

[0096] (6) The hollow microspheres C are heat treated in a 5% H2-95% Ar atmosphere at 500°C for 3 h to obtain the target product, which is a hollow microsphere with low thermal conductivity and low emissivity (the shell layer is a glass ball shell layer, a porous silicon oxide layer and a metal layer arranged in sequence from the inside to the outside).

[0097] The mass percentages of the glass shell layer, porous silicon oxide layer and metal layer in the hollow microspheres obtained in this example are 66.7%, 20% and 13.3% respectively. Other structural and performance parameters are shown in Table 1.

[0098] Example 4

[0099] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0100] The density is 0.38g / cm 3 Glass hollow microspheres.

[0101] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0102] (2) adding 4 g of the hollow microspheres A obtained in step (1) to a treatment solution A composed of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0103] (3) adding a mixed solution containing 6.4 mL of tetraethyl orthosilicate and 16 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0104] (4) 10 g of cobalt nitrate, 7 g of sucrose and 5 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution B;

[0105] (5) The hollow microspheres B obtained in step (3) were mixed with 9 g of treatment solution B, and then treated at 500° C. for 60 min in an air atmosphere. After the reaction, the microspheres were dispersed through an 80-mesh sieve to obtain hollow microspheres C;

[0106] (6) The hollow microspheres C are heat treated in a 5% H2-95% Ar atmosphere at 500°C for 3 h to obtain the target product, which is a hollow microsphere with low thermal conductivity and low emissivity (the shell layer is a glass ball shell layer, a porous silicon oxide layer and a metal layer arranged in sequence from the inside to the outside).

[0107] The mass percentages of the glass shell layer, porous silicon oxide layer and metal layer in the hollow microspheres obtained in this example are 62.5%, 25% and 12.5% ​​respectively. Other structural and performance parameters are shown in Table 1.

[0108] Example 5

[0109] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0110] The density is 0.30g / cm 3 Glass hollow microspheres.

[0111] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0112] (2) adding 4 g of the hollow microspheres A obtained in step (1) to a treatment solution A composed of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0113] (3) adding a mixed solution containing 3.2 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0114] (4) 10 g of copper nitrate, 7 g of sucrose and 5 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution B;

[0115] (5) The hollow microspheres B obtained in step (3) were mixed with 6.8 g of treatment solution B, and then treated at 400° C. for 60 min in an air atmosphere. After the reaction, the microspheres were dispersed through an 80-mesh sieve to obtain hollow microspheres C;

[0116] (6) The hollow microsphere C was heat treated in a 5% H2-95% Ar atmosphere at 600°C for 3 hours to obtain the target product, the hollow microsphere with both low thermal conductivity and low emissivity (the shell layer is sequentially arranged from the inside to the outside, including a glass ball shell layer, a porous silicon oxide layer, and a metal layer). The low-magnification SEM image of the hollow microsphere is shown in FIG. Figure 3 As shown in the high magnification SEM image Figure 4 As shown in the figure, the hollow microspheres have a perfect spherical shape, and their surface is rough with a large number of protrusions; the enlarged SEM image shows that the surface of the microspheres (i.e., the surface of the outermost metal shell) is composed of independent island particles.

[0117] The X-ray diffraction pattern of the hollow microspheres is shown in Figure 5 As shown in the figure, the X-ray diffraction pattern contains two peaks, the low A peak is the diffraction peak of amorphous silicon dioxide, and the three sharp B peaks are the diffraction peaks of metallic copper.

[0118] The mass percentages of the glass shell layer, porous silicon oxide layer and metal layer in the hollow microspheres obtained in this example are 71.4%, 14.3% and 14.3% respectively. Other structural and performance parameters are shown in Table 1.

[0119] Example 6

[0120] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0121] The density is 0.25g / cm 3 Glass hollow microspheres.

[0122] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0123] (2) adding 4 g of the hollow microspheres A obtained in step (1) to a treatment solution A composed of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0124] (3) adding a mixed solution containing 3.2 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0125] (4) 10 g nickel nitrate, 7 g sucrose and 5 g water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution B;

[0126] (5) The hollow microspheres B obtained in step (3) were mixed with 13.5 g of treatment solution B, and then treated at 500° C. for 60 min in an air atmosphere. After the reaction, the microspheres were dispersed through an 80-mesh sieve to obtain hollow microspheres C;

[0127] (6) The hollow microspheres C are heat treated in a 5% H2-95% Ar atmosphere at 500°C for 3 h to obtain the target product, which is a hollow microsphere with low thermal conductivity and low emissivity (the shell layer is a glass ball shell layer, a porous silicon oxide layer and a metal layer arranged in sequence from the inside to the outside).

[0128] The mass percentages of the glass shell layer, porous silicon oxide layer and metal layer in the hollow microspheres obtained in this example are 66.7%, 13.3% and 20% respectively. Other structural and performance parameters are shown in Table 1.

[0129] Example 7

[0130] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0131] The density is 0.20g / cm 3 Glass hollow microspheres.

[0132] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0133] (2) adding 4 g of the hollow microspheres A obtained in step (1) to a treatment solution A composed of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0134] (3) adding a mixed solution containing 3.2 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0135] (4) 10 g nickel nitrate, 7 g sucrose and 5 g water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution B;

[0136] (5) The hollow microspheres B obtained in step (3) were mixed with 13.5 g of treatment solution B, and then treated at 500° C. for 60 min in an air atmosphere. After the reaction, the microspheres were dispersed through an 80-mesh sieve to obtain hollow microspheres C;

[0137] (6) The hollow microspheres C are heat treated in a 5% H2-95% Ar atmosphere at 500°C for 3 h to obtain the target product, which is a hollow microsphere with low thermal conductivity and low emissivity (the shell layer is a glass ball shell layer, a porous silicon oxide layer and a metal layer arranged in sequence from the inside to the outside).

[0138] The mass percentages of the glass shell layer, porous silicon oxide layer and metal layer in the hollow microspheres obtained in this example are 66.7%, 13.3% and 20% respectively. Other structural and performance parameters are shown in Table 1.

[0139] Comparative Example 1

[0140] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0141] The density is 0.38g / cm 3 Glass hollow microspheres.

[0142] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0143] (2) adding 4 g of the hollow microspheres A obtained in step (1) to a treatment solution A composed of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0144] (3) adding a mixed solution containing 4.8 mL of tetraethyl orthosilicate and 13 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0145] (4) The hollow microspheres B obtained in step (3) are treated in an air atmosphere at 500° C. for 60 min, and then heat treated in a 5% H2-95% Ar atmosphere at 500° C. for 3 h to obtain the target product, glass-porous silica hollow microspheres.

[0146] The mass percentages of glass and silicon dioxide layers in the glass-porous silicon oxide hollow microspheres obtained in this comparative example are 76.8% and 23.2% respectively. Other structural and performance parameters are shown in Table 1.

[0147] Comparative Example 2

[0148] Preparation of glass-porous silica-metal hollow microspheres, the specific implementation scheme is as follows:

[0149] The density is 0.38g / cm 3 Commercial glass hollow microspheres.

[0150] (1) Flotation of glass hollow microspheres: Mix glass hollow microspheres and water at a volume ratio of 1:4, stir, and allow to stand for stratification before taking out the upper floating microspheres, filtering them, and drying them to obtain hollow microspheres A.

[0151] (2) 10 g of cobalt nitrate, 7 g of sucrose and 5 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution B;

[0152] (3) 4 g of the hollow microspheres A obtained in step (1) were mixed with 9 g of the treatment solution B, and then treated at 500° C. for 60 min in an air atmosphere. After the reaction, the hollow microspheres D were dispersed through an 80-mesh sieve.

[0153] (4) The hollow microspheres D were heat treated in a 5% H2-95% Ar atmosphere at 500°C for 3 h to obtain the target product, glass-metal hollow microspheres.

[0154] The mass percentages of glass and metal in the glass-metal hollow microspheres obtained in this comparative example are 83.3% and 16.7% respectively. Other structural and performance parameters are shown in Table 1.

[0155] Comparative Example 3

[0156] A method for preparing hollow microspheres with both low thermal conductivity and low emissivity, the specific implementation scheme is as follows:

[0157] The density is 0.30g / cm 3 Glass hollow microspheres.

[0158] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water are mixed at a volume ratio of 1:4, stirred, and allowed to stand for stratification before taking out the floating microspheres on the upper layer, filtering them, and drying them to obtain hollow microspheres A;

[0159] (2) adding 4 g of the hollow microspheres A obtained in step (1) to a treatment solution A composed of 2.00 g of hexadecyltrimethylammonium bromide, 80 mL of water, 100 mL of anhydrous ethanol, 10 mL of concentrated ammonia water and 0.03 g of sodium chloride, and stirring for 5 min to obtain a mixed solution containing microspheres;

[0160] (3) adding a mixed solution containing 3.2 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol to the mixed solution containing microspheres obtained in step (2) at a rate of 5 mL / h, stirring at room temperature for 30 min, filtering, and drying to obtain hollow microspheres B;

[0161] (4) treating the hollow microspheres B obtained in step (3) at 400° C. for 60 min in an air atmosphere, and dispersing through an 80-mesh sieve after the reaction to obtain hollow microspheres C;

[0162] (5) The hollow microspheres C (1 g / 20 ml) obtained in step (4) were treated in turn with solution C1: 1.6 mol / L hydrochloric acid, 35 g / L stannous chloride; solution C2: 0.5 mol / L hydrochloric acid, 0.015 mol / L palladium chloride, stirred at 40°C for 20 min, filtered, dried at 60°C, and sieved to remove agglomerated particles to obtain hollow microspheres D;

[0163] (6) The hollow microspheres D (1 g / 70 ml) obtained in step (5) were treated in solution D, wherein the reaction solution contained 0.05 mol / L copper sulfate, 0.04 mol / L potassium sodium tartrate, 0.03 mol / L EDTA, 0.25 mol / L sodium hydroxide, and 3 ml / L formaldehyde. The mixture was stirred at room temperature and filtered after the reaction was completed. The mixture was dried at 60° C. to obtain the final product, the hollow microspheres.

[0164] The glass shell layer, porous silicon oxide layer and metal layer in the hollow microspheres obtained in this comparative example are all continuous layer structures, and the mass percentages of each layer are 71.5%, 14.1% and 14.4% respectively. Other structural and performance parameters are shown in Table 1.

[0165] Table 1 Structure and performance parameters of the hollow composite microsphere samples obtained in each embodiment

[0166]

[0167] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A hollow microsphere having both low thermal conductivity and low emissivity, characterized in that: The structure of the hollow microsphere comprises a hollow core, and a glass shell layer, a porous silicon oxide layer and a metal layer arranged in sequence from the inside to the outside; The metal layer is composed of a plurality of metal regions which are physically isolated from each other.

2. The hollow microsphere according to claim 1, characterized in that: The metal coverage of the metal layer is 30-70%; and / or The metal region is composed of one or more of metals selected from nickel, cobalt, iron, copper and silver.

3. The hollow microsphere according to claim 1, characterized in that: Calculated by mass percentage, the hollow microspheres contain 45-80wt% of a glass shell layer, 10-35wt% of a porous silicon oxide layer and 10-35wt% of a metal layer.

4. The hollow microsphere according to claim 1, characterized in that: The density of the hollow microspheres is 0.25-0.9 g / cm 3 , average diameter is 15-80μm, specific surface area is 50-200m 2 / g.

5. The hollow microsphere according to claim 1, characterized in that: The porous silicon oxide layer is made of porous silicon dioxide, the porosity of the porous silicon dioxide is 59.8%, and the average pore size is 2.7 nm.

6. The method for preparing hollow microspheres according to any one of claims 1 to 5, characterized in that: The steps include: Assembling porous silicon oxide precursor on the surface of glass hollow microspheres to obtain microspheres A; The metal precursor is coated on the surface of microsphere A to obtain microsphere B; The microspheres B are heat-treated in a reducing atmosphere to obtain the hollow microspheres.

7. The preparation method according to claim 6, characterized in that: The method for assembling a porous silicon oxide precursor on the surface of a glass hollow microsphere to obtain microsphere A comprises the following steps: After mixing the glass hollow microspheres with the treatment solution A, a mixed solution of tetraethyl orthosilicate and anhydrous ethanol is added, and then reacting at room temperature for 20-60 minutes to obtain the microspheres A; The treatment solution A is composed of 1-3 g hexadecyltrimethylammonium bromide, 50-100 mL water, 60-120 mL anhydrous ethanol, 8-15 mL concentrated ammonia water and 0.02-0.05 g sodium chloride; The mass ratio of the glass hollow microspheres to the hexadecyltrimethylammonium bromide in the treatment solution A is 2:1; The volume ratio of water to tetraethyl orthosilicate and anhydrous ethanol in the treatment liquid A is 80:(2-10):(10-25).

8. The preparation method according to claim 6, characterized in that: The method for coating the surface of microsphere A with a metal precursor to obtain microsphere B comprises the following steps: After mixing the microsphere A with the treatment liquid B, reacting them in an air atmosphere at a temperature of 400-600° C. for 60 minutes to obtain the microsphere B; The treatment liquid B is obtained by mixing a soluble metal salt with a water-soluble organic matter and water in a mass ratio of 10:(6-9):

5.

9. The preparation method according to claim 6, characterized in that: The reducing atmosphere is hydrogen or a mixture of hydrogen and argon; and / or The heat treatment temperature is 400-600° C., and the heat treatment time is 1-6 hours.

10. Use of the hollow microspheres according to any one of claims 1 to 5 in powder thermal insulation and thermal insulation fillers.

Citation Information

Patent Citations

  • Method for measuring isostatic pressure resistance of hollow glass beads

    CN103954506A

  • High-strength hollow composite microsphere with three-layer spherical shell structure as well as preparation method and application of high-strength hollow composite microsphere

    CN114345249A

  • Composite hollow microsphere with three-layer spherical shell structure as well as preparation method and application of composite hollow microsphere

    CN114381037A

  • Lightweight flexible thermal insulation material with low absorption ratio and high emissivity and preparation method thereof

    CN115232341A

  • Composite hollow microsphere with layered composite spherical shell structure as well as preparation method and application of composite hollow microsphere

    CN115337878A